2003
DOI: 10.1080/0963828021000031197
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Dutch version of QUEST 2.0 with users of various types of assistive devices

Abstract: D-QUEST (and therefore also QUEST) proves itself to be a highly applicable, reliable and valid instrument to assess user-satisfaction of users of all kinds of assistive device provisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 6 publications
3
68
0
Order By: Relevance
“…The 12 items of QUEST 2.0 were then analyzed with factor analysis, which showed that the underlying structure of satisfaction consists of two key dimensions: satisfaction with specific features of the assistive technology device and satisfaction with consumer service aspects of assistive technology (Demers et al, 2001). QUEST 2.0 was developed in Canadian English and French and then translated into several languages (Fucelli and Andrich, 2002;Wessels and Witte, 2003;Chan and Chan, 2006;Mao et al, 2010;Magnusson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The 12 items of QUEST 2.0 were then analyzed with factor analysis, which showed that the underlying structure of satisfaction consists of two key dimensions: satisfaction with specific features of the assistive technology device and satisfaction with consumer service aspects of assistive technology (Demers et al, 2001). QUEST 2.0 was developed in Canadian English and French and then translated into several languages (Fucelli and Andrich, 2002;Wessels and Witte, 2003;Chan and Chan, 2006;Mao et al, 2010;Magnusson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…9 The respondent is asked to rate his or her satisfaction with the manual wheelchair with respect to 13 different aspects using a five-point scale.…”
Section: Personal and Lesion Characteristicsmentioning
confidence: 99%
“…Dutch version of the Quebec user evaluation of satisfaction with assistive technology D-QUEST consists of a written questionnaire 9 and proved to be a reliable and valid instrument. 9 The respondent is asked to rate his or her satisfaction with the manual wheelchair with respect to 13 different aspects using a five-point scale.…”
Section: Personal and Lesion Characteristicsmentioning
confidence: 99%
“…The ratings of the Device subscale score, Service subscale score and Total QUEST score had a mean value >4, which represents a very high overall satisfaction. Wessels & de Witte [49] analyzed satisfaction with the QUEST in a group of individuals using unspecified orthoses and shoe adaptations. In this group, the mean satisfaction with the device was only 3.9 compared to 4.4 in our study, and the satisfaction with the service was also lower than in our sample (3.8 vs. 4.8).…”
Section: E-mag Locked E-mag Unlocked Significantmentioning
confidence: 99%